Study on tuberization of Rehmannia glutinosa (Gaertn.) Libosch - Hoai Sam, Vu; Thi Xuyen, Nguyen; Thi Huong, Nguyen; Thi Ngoc Anh, Duong; Minh Tuyen, Nguyen; Duy Phuong, Nguyen; Thuy Hien, Phan (Vietnam Journal of Biotechnology, 2020)
Rehmannia glutinosa (Gaertn.) Libosch. is an herbal plant, which belongs to the Srcophulariaceae family, containing the main active ingredients such as catalpol and verbacoside in its root tubers. In traditional medicine, R. glutinosa tubers have been used in the fresh or dried tuber root or the prepared rehamannia root. They not only possess the comprehensive pharmacological actions in the blood system, endocrine system but also used mainly for anti-tumor treament, immune-enhancement, anti-diabetes, treament for concretion in the urinary tract, etc. R. glutinosa is naturally distributed in China, Korea and Japan. This species was introduced into Viet Nam since 1958 and then planted widely in many the Northern plain and midland provinces. In Vietnam, R. glutinosa produces flowers without seeds, therefore the plant has been mainly propagated by slicing tubers. In this work, we investigated the effect of some plant hormones and sucrose contents on the ability to producing microtubers of R. glutinosa. Experiments were establishmented on the 1/4 MS medium supplemented with 50g/L sucrose.  Results showed that auxin (IBA, NAA) had no effect on the in vitro tuber formation of R. glutinosa. The efficiency of using the single BAP or PP333 was low. The highest in vitro tuberization rate of R. glutinosa obtained on the medium supplemented with the combination of BAP (1.0 mg/L) and PP333  (0.3 mg/L), reached 83.33% and the number of tubers/plant was 5.58. The optimal sucrose concentration for increasing the diameter and weight of microtubers was 70 g/L. 100% of plants with tuber-roots survived in the nursery and thrived on the field